Does Payoff Equity Facilitate Coordination? A test of Schelling's Conjecture - Raúl López-Pérez; Ágnes Pintér; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Starting from Schelling (1960), several game theorists have conjectured that payoff equity might facilitate coordination in normal-form games with multiple equilibria ?the more equitable equilibrium might be selected either because fairness makes it focal or because many individuals dislike payoff inequities, as abundant experimental evidence suggests. In this line, we propose a selection principle called Equity (EQ), which selects the equilibrium in pure strategies minimizing the difference between the highest and smallest payoff, if only one such equilibrium exists. Using a within-subjects experimental design, furthermore, we study the relative performance of the equity principle in six simple 2x2 coordination games. Overall, we find that Equity explains individual behavior better than a large range of alternative theories, including theories of bounded rationality and several other equilibrium selection principles. Further, a classification analysis suggests the existence of two main groups of players: (i) players who tend to play as Equity predicts, and (ii) a miscellaneous group of players who either go for the risk dominant equilibrium or act in a boundedly rational manner. This heterogeneity seems to be behind most of the coordination failures that we observe.
Keywords: C72; C91; D03; D63; 330; Coordination; equity; experiments; inequity aversion; level-k thinking; risk dominance